2020
DOI: 10.3390/ijfs8030042
|View full text |Cite
|
Sign up to set email alerts
|

Bank-Specific and Macroeconomic Determinants of Profitability: A Revisit of Pakistani Banking Sector under Dynamic Panel Data Approach

Abstract: This study aims to examine the effect of the bank-specific and macroeconomic determinants of profitability for the banking sector of Pakistan. To incorporate the issues of endogeneity, unobserved heterogeneity, and profit persistence, we apply a generalised method of moments (GMM) technique under the Arellano–Bond framework to a panel of Pakistani banks that covers the period 2003–2017. The results of a dynamic panel data approach reveal that capital adequacy accelerates the profitability of the bankin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
30
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(37 citation statements)
references
References 74 publications
3
30
0
4
Order By: Relevance
“…Liquidity ratio, business mix indicators, interest rates, and industrial production deteriorates bank profitability. Liquidity risks enhance the probability of default risks and transmit into the unpaid loans and lower returns (Rahman et al, 2020). This study shows unusual results, namely that interest rates and business mix reduce bank profitability.…”
Section: Literatur Review Determinants Banks' Profit In Developing Marketmentioning
confidence: 72%
“…Liquidity ratio, business mix indicators, interest rates, and industrial production deteriorates bank profitability. Liquidity risks enhance the probability of default risks and transmit into the unpaid loans and lower returns (Rahman et al, 2020). This study shows unusual results, namely that interest rates and business mix reduce bank profitability.…”
Section: Literatur Review Determinants Banks' Profit In Developing Marketmentioning
confidence: 72%
“…Rezina et al (2020) found the GDP growth and real interest rate to have a positive effect on profitability (ROA), whilst inflation was found to exert a negative impact on profitability. Focusing on the banking industry in Pakistan, Rahman et al (2020) employed the GMM estimation technique in verifying the determinants of profitability from 2003 to 2017. The study revealed that macroeconomic variables such as the interest rate and industrial production exert negative influence on profitability.…”
Section: Overview Of the Literaturementioning
confidence: 99%
“…Further review of related empirical studies examining factors or conditions responsible for variability in corporate/firm performance, suggests that most of such studies are dominated by how aggregate macroeconomic variables or conditions, and firm-specific or industry-specific factors influence corporate/firm performance. (see Adams et al, 2005;Asimakopoulos et al, 2009;Apadore and Zainol, 2014;Palaniappan, 2017;Mahadalle and Kaplan, 2017;Doruk, 2019;Rahman et al, 2020). For instance, an in-depth review of the extant literature on corporate or firm performance suggests that most studies examining the relationship in question focus primarily on the role of aggregate macroeconomic conditions or variables such as the gross domestic product (GDP) growth, inflation, exchange rate, etc., and firm-specific factors such as size, form of leadership, etc.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…See Chakane, Chaskar, Patil, Shelar and Godse (Chakane et al 2017) for the further details on the nexus between automated information system and the crop management. Also see Rahman, Yousaf and Tabassum (Rahman et al 2020) for the discussion on industrial production.] In this mechanism, the labour efficiency reduces the labour cost (Blanchard 2017), which is a critical component of the per-unit cost.…”
Section: Introductionmentioning
confidence: 99%